PENTINGNYA BELAJAR MANDIRI BAGI PESERTA DIDIK DI PERGURUAN TINGGI - Vitamaya Oishi, Ivonne Ruth (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2019)
Self directed learning of students to do independent learning which is one way to improve skills in the learning process that are very necessary to obtain good and more optimal learning outcomes. Students are expected to experience behavioral changes in cognitive (knowledge), affective (attitude) and psychomotor (skill) aspects. The ability to Self directed learning plays a role in forming students in order to have lifelong learning abilities.